Use of antidepressants during pregnancy among women in Iceland 2003 - 2012: A nationwide population-based study - Dagný Baldvinsdóttir 1968- (2016)
Antidepressant use during pregnancy has increased during the past decades, especially in the West. In this study, we aimed to describe the prevalence of antidepressant use during pregnancy among women in Iceland 2003 – 2012, according to maternal and pregnancy-related characteristics. This is a nationwide population-based drug utilization study based on data from the National Medicines Registry and the Medical Birth Registry in Iceland. The study population comprised all pregnancies in Iceland that resulted in either a live birth or a stillbirth after gestational week 22 from January 1st 2003 through December 31st 2012 (N = 44775). Antidepressant exposure was defined as one or more dispensed drugs from 90 days before the last menstrual period (LMP) until delivery and accorded to the World Health Organization Anatomic Therapeutic Chemical classification system (N06A). Co-medication of anxiolytics (N05B) and hypnotics and sedatives (N05C) was assessed. Overall, 3658 (8.2%) of 44,775 pregnancies were exposed to antidepressants during pregnancy. The youngest women (<25 years) and oldest women (>35 years) had a higher prevalence (9.1%, 9.6%) of antidepressant use than women between 25 – 35 years (7.5%), while prevalence of use increased with parity (0, 1, 2, >2) with a prevalence of 7.0%, 7.8%, 9.8% and 13.8% respectively. Antidepressant use was higher among single women than among those cohabiting (14.4% vs. 7.0%). The annual prevalence of antidepressant use varied by study year, from 7.5% to 9.5%. Selective serotonin reuptake inhibitors (SSRIs) were the most commonly used antidepressants, with 3158 (7.0%) exposed pregnancies. The prevalence of antidepressant use decreased with each passing trimester of pregnancy; from 6.1% before LMP to 4.5%, 3.6% and 2.9% in 1st, 2nd and 3rd trimesters respectively. In about one-third of exposed pregnancies, women were also dispensed anxiolytics, hypnotics or sedatives. In line with an overall widespread use of antidepressants in Iceland, use among pregnant women was ...